"Revitalizing" degraded solid oxide fuel cells in sour fuels for bifunctional oxygen catalysis in zinc–air batteries. Issue 18 (8th September 2020) - Cao, Xiaojuan; Yang, Ying; Yan, Xiaoyu; Geels, Norbert J.; Luo, Jing-Li; Yan, Ning
Abstract : "Trash to treasure": degraded solid oxide fuel cells can be "revitalized" as high-performance bifunctional catalysts. Abstract : Electrochemical devices are central to sustainable energy storage and conversion. Currently, most of the spent devices end up in landfills or the conventional toxic and energy-intensive metal extraction processes. Advanced reuse and re-valorization practices are lacking due to both technical and economic barriers. To address this growing concern, we herein demonstrate that the fully degraded electrode of the state-of-the-art anode-supported solid oxide fuel cells (SOFCs) can be "revitalized" in situ during the operation. The facile treatment involves fueling the SOFC with the readily available fuels containing H2 S and the electrode pulverization. The resulting powder comprises porous particles with mixed nickel sulfide nanoclusters dispersed on Y-stabilized ZrO2 (NiS x /YSZ) which enables superior activity in both the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Its voltage gap between the ORR half-wave potential and OER potential at the benchmark 10 mA cm −2 reached 0.74 V, rendering stable and efficient performance in a rechargeable Zn–air battery. This work might boost the awareness of treating end-of-life electrochemical materials sustainably and pave new ways for the circular economy.